Affirmative Action in Indian Higher Education - Nandi, Emon; Pathak, Binay (International Higher Education, 2024)
In India, the affirmative action policy is commonly known as the reservation policy, which applies to legislature, education, and employment. The reservation policy attempts to mitigate the adverse impact of the historical deprivation faced by India’s socially and economically backward classes. Although it helped some of the marginalized groups to improve their economic conditions by ensuring equal opportunities in higher education, it might fall short in terms of their impact on social integration.